Not all rounds are committees self-defense and vice versa Types of peasant patrols - korsbaek, Leif (2011)
Ihe general features of instirution known as la ronda campesina are prcscnrcd in rhc "tesen! rcxt - irs origin, irs hisrory, its distriburion and irs characrerisrics. Bur argllmenrs are furrhercd in favor of disri nguishing rhc di ffett!nt types of rondas campesinas, as rhey possess very different social ami cultural dynamics. Four [ypes of rondas campesinas are brought forward: rhc original rondas campesinas rhar were born in various northcrn rcgions, wherc rhe land reform had bcen eHicknl and rhe pcasanrs wcrc srnallholdcrs, rhc rondas campesinas in pcasanr communitics wirh communal landholdiug, rhc rondas campesinas in rhe Amazon jungle, and finally rhe socallcd comírés do: aurodefensa, crcared from abovc, by [he govcrnmcnr.